Postharvest lactic acid treatment on cauliflower - Parco, Lalyn N.; Azanza, Ma. Patricia V. (1997.)
The general objective of this study is to extend the shelf life of cauliflowers using lactic acid spray treatments. The use of lactic acid in freshly harvested fruits and vegetable might offer an alternative way to extend the shelf life of food commodities without imparting any deleterious effect on human health. The first phase of this study dealt with the determination of an optimum concentration of lactic acid solution that could extend the shelf life of cauliflowers. The concentrations of lactic acid solutions were 0.1, 0.2 and 0.3% v/v with a contact time of 1 min. Spraying was the technique used to deliver the test solutions to the cauliflower samples. Quality assessment included tests for microbial and physico-chemical qualities of samples stored for 21 days under refrigerated conditions. The physico-chemical tests done included the pH determination, curd and stem texture determinations. The microbiological tests done included Total Plate Count and Yeast and Molds Count determinations. Sampling was done at 0, 3, 9, 15 and day 21 of storage at refrigerated condition. The test lactic acid concentrations used for the spray-treatments of cauliflowers did not have significant effects on the pH, the firmness quality of curds and stems and the Yeasts and Mold Counts of the samples during 21 days of refrigerated storage. The Total Plate Count of all treated samples were significantly lower than that of the untreated control. Treatment using 0.3% lactic acid was chosen as the optimum concentration of lactic acid for spray-treatment of cauliflower since it gave the lowest TPC among the treated samples. The second phase of this study dealt with the determination of an optimum contact time using optimum concentration of lactic acid solution selected in Phase 1. The different test contact times of 1, 2 and 3 min did not cause significant effects on the pH and Yeasts and Molds Count of the samples. The different test contact times using 0.3% v/v of lactic acid caused significant effects on the texture qualities of stem and curd and had significantly reduced the Total Plate Count of the samples as compared to the untreated control. However, there was no detected significant differences on the efficacy of lactic acid treatment using 1,2 and 3 min as contact time.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Vegetables -- Preservation; Cauliflower